Preproinsulin designer antigens excluded from endoplasmic reticulum suppressed diabetes development in nod mice by dna vaccination - Stifter, Katja (2019)
DNA vaccines against autoimmune type 1 diabetes (T1D) contain a nonpredictable risk to induce autoreactive T cell responses rather than a protective immunity. Little is known if (and how) antigen expression and processing requirements favor the induction of autoreactive or protective immune responses by DNA immunization. Here, we analyzed whether structural properties of preproinsulin (ppins) variants and/or subcellular targeting of ppins designer antigens influence the priming of effector CD8+ T cell responses by DNA immunization. Primarily, we used H-2b RIP-B7.1 tg mice, expressing the co-stimulator molecule B7.1 in beta cells, to identify antigens that induce or fail to induce autoreactive ppins-specific (Kb/A12-21 and/or Kb/B22-29) CD8+ T cell responses. Female NOD mice, expressing the diabetes-susceptible H-2g7 haplotype, were used to test ppins variants for their potential to suppress spontaneous diabetes development. We showed that ppins antigens excluded from expression in the endoplasmic reticulum (ER) did not induce CD8+ T cells or autoimmune diabetes in RIP-B7.1 tg mice, but efficiently suppressed spontaneous diabetes development in NOD mice as well as ppins-induced CD8+ T cell-mediated autoimmune diabetes in PD-L1−/− mice. The induction of a ppins-specific therapeutic immunity in mice has practical implications for the design of immune therapies against T1D in individuals expressing different major histocompatibility complex (MHC) I and II molecules.